A survey of impact on industrial parks caused by the 2011 Great East Japan earthquake and tsunami. (November 2017) - Yu, Junlei; Cruz, Ana Maria; Piatyszek, Eric; Lesbats, Michel; Tardy, Alicja; Hokugo, Akihiko; Tatano, Hirokazu
Abstract: During the 2011 Great East Japan Earthquake and Tsunami (GEJET), many industrial facilities were affected to different extents by the earthquake and/or tsunami. Damages and reasons for hazardous materials releases were reported by former studies. This paper provides further details concerning the impact of GEJET, by the data collected from a series of field visits, interviews and mail surveys. In this study, we report the facility damage and economic losses, the performance of safety and mitigation measures, the emergency preparedness and response to the chemical releases triggered by earthquake and/or tsunami, and changes to preparedness practices at the facilities after experiencing the GEJET. Recommendations are proposed at the end when compared to previous studies in the literature. Highlights: The earthquake and/or tsunami during the GEJET had caused substantial damages and economic losses to the industries investigated. The investigated industries were less prepared for the tsunami impact. Loss of electricity was reported as a major problem affecting operations at storage tanks and vessels, and pipeline systems. Process units and atmospheric storage tanks were more vulnerable than other types of equipment. Public communication programs on hazardous materials accidents preparedness were not available for most surveyed facilities.